Learners’ Affection and Cognition: Their Interrelationship in Learning English - Lilis Natalia Totong; Markus Deli Girik Allo; Eka Prabawati Rum; Muh. Putra Pratama (Indonesian TESOL Journal, 2024)
Cognition is often used to find out how far someone has mastered the material that has been taught by educational goals. In addition to mastery of teaching materials, cognition is also influenced by affection. Students' affection in learning English varies, there are students who show good affection, namely students feel happy and are active in taking part in the learning process. There are also those who show an affection that is not happy with the learning process, has an indifferent affection (apathy), is not active, talks to themselves and does not pay attention to the teacher's explanation. This study aims to determine how the correlation between the learners’ affection and cognition in learning English. This type of research is correlational research. The population of this study were all eighth-grade students at Makale Christian Junior High School, which amounted to 168 students. The sampling technique used was cluster random sampling. Based on the cluster random sampling technique, the class used as a sample is class VIII A as many as 32 students. The instrument used in this research is to use a questionnaire and a test. Pearson Product Moment correlation test is used to determine the correlation between affection and cognition. Based on the correlation test, the correlation coefficient value is 0.144. Because the value of r count is lower than the value of r table (0.140 < 0.286) then there is a negative correlation between learners’ affection and cognition which are in the exceptionally low category. This means that the lower the student's affection the lower the result of learning English.